Stress Distribution Pattern in Mini Dental Implant-Assisted RPD with Different Clasp Designs: 3D Finite Element Analysis - Chaiy Rungsiyakull; Pimduen Rungsiyakull; Kullapop Suttiat; Nut Duangrattanaprathip (Hindawi Limited, 2022)
Introduction. The removable partial denture (RPD) components, especially the retentive arm, play a major role in the loading characteristic on supporting structures. Objective. To evaluate and compare the effect of different clasp designs on the stress distribution pattern, maximum von Mises stress, and average hydrostatic pressure on abutment teeth, as well as edentulous ridges, mini dental implants (MDIs), and peri-implant bone between the conventional removable partial denture (CRPD) and mini dental implant-assisted distal extension removable partial denture (IARPD) using a three-dimensional finite element analysis (3D FEA). Materials and Methods. 3D FEA models of mandibular arches, with and without bilateral MDI at the second molar areas, and Kennedy class I RPD frameworks, with RPA, RPI, Akers, and no clasp component, were generated. A total of 200 N vertical load was bilaterally applied on both sides of distal extension areas, and the stress was analyzed by 3D FEA. Results. The stress concentration of IARPD with RPI clasp design was located more lingually on abutment teeth, MDI, and peri-implant bone, while the other designs were observed distally on the supporting structures. The maximum von Mises stress on the abutment root surface was decreased when the RPDs were assisted with MDIs. The CRPD and IARPD with the Akers clasp design showed the highest von Mises stress followed by the designs with RPA and RPI clasp, respectively. The average hydrostatic pressure in each group was in approximation. Conclusion. The placement of MDIs on distal extension ridges helps to reduce the stress concentration on denture supporting structures. The maximum von Mises stress is affected by the different designs of clasp components. The CRPD and the IARPD with RPI clasp provide the least stress on supporting structures.